COVID-19 booster dose acceptance, hesitancy and concerns among the elderly population: A cross-sectional study - Imran, Muhammad; Ahmed, Zeeshan; Ishaqui, Azfar Athar; Bafail, Duaa; Ahmad, Salman Ashfaq; Farooq, Javeria; Ali, Imran; Mustafa, Bilal; Zehra, Tabassum; Jaweed, Lailoona; Kapadia, Samreen; Ahmed, Salman; et al. (The Journal of Infection in Developing Countries, 2023)
Introduction: The COVID-19 pandemic that originated in Wuhan, China in December 2019 results in respiratory and gastrointestinal infections. Elderly patients are at high risk. Preventive measures like avoiding contact with COVID-19 patients and wearing N95 masks can contribute to reducing the risk of infection, but vaccination remains crucial. Methodology: A cross-sectional survey-based study was conducted among the elderly population (≥ 50 years) in Pakistan. A 16-items questionnaire explored the socio-demographic profile of the participants, including questions about their age, gender, etc. The other sections included questions regarding vaccine registration, vaccine acceptance, and hesitation and fears towards vaccines. The items were developed to collect the data on the basis of the Likert scale. Results: There was a total of 3059 respondents. The majority of the participants (n = 2726, 89.1%) were aged below 70 years, while 10.9% (n = 333) were aged above 70 years. Many participants (47.1%) expressed their concerns about the efficacy of COVID-19 vaccine booster dose. Despite their willingness to vaccinate with the cOVID-19 vaccine, 24.7% female participants expressed concerns related to the safety of the vaccine. Among all the respondents, 23.1% participants had no concerns about the cOVID-19 vaccine booster dose. The study identified a reluctance and lack of confidence in the efficiency of the COVID-19 booster dose. Conclusions: The alarming situation is rigidity towards vaccination among the elderly population. Necessary measures must be taken by the health department of Pakistan to manage this reluctant behavior and increase confidence on the efficiency of the COVID-19 booster dose.